DEC fuel cell‐based universal power compensator for dual PCC system. (2nd February 2021) - Patnaik, Nishant; Panda, Anup Kumar; Mohanty, Pratap Ranjan; Pandey, Richa
Summary: This article proposes a special type of power conditioning system, termed as UPC (Universal Power Compensator) for a three‐phase four wire system to take care of several power quality aspects as well as supply interruption conditions, suitable for combination of different load coupling points, that is, PCC (point of common coupling). Two different PCCs are considered in the system, out of which one is a voltage sensitive point. UPC consist of a special UPQC arrangement, termed as left‐shunt UPQC and an external (independent) power source such as a fuel cell system (FCS) that includes fuel cell stack with DC‐DC converter. This arrangement prevents the effect of voltage disturbance on sensitive load point in addition to mitigating the current harmonic contamination from both the load points. The control structure for UPQC is based on direct DC‐link voltage control and is of prime importance and has been suitably adopted for the proposed arrangement. Also, a dynamic evolution control (DEC) algorithm is proposed for FCS of UPC for quick response under transient conditions, such as connection instant and load changes. Various performance domains such as harmonic compensation, voltage compensation, neutral current compensation and supply compensation of UPC are analyzed using simulation analysis with MATLAB/SIMULINK. Also, a comparative performance analysis is illustrated to indicate the superiority of DEC‐FC system. Abstract : This article proposes a special type of power conditioning system, termed as UPC (Universal Power Comspensator) for a three‐phase four wire system to take care of several power quality aspects as well as supply interruption conditions, suitable for combination of different load coupling points, that is, PCC (point of common coupling).